2016
DOI: 10.1002/jssc.201600671
|View full text |Cite
|
Sign up to set email alerts
|

Ionic-liquid-based dispersive liquid-liquid microextraction combined with magnetic solid-phase extraction for the determination of aflatoxins B1, B2, G1, and G2in animal feeds by high-performance liquid chromatography with fluorescence detection

Abstract: A novel two-step extraction technique combining ionic-liquid-based dispersive liquid-liquid microextraction with magnetic solid-phase extraction was developed for the preconcentration and separation of aflatoxins in animal feedstuffs before high-performance liquid chromatography coupled with fluorescence detection. In this work, ionic liquid 1-octyl-3-methylimidazolium hexafluorophosphate was used as the extractant in dispersive liquid-liquid microextraction, and hydrophobic pelargonic acid modified Fe O magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Sample purification methods included LLE [30][31][32][33], and SPE [34][35][36][37]. Considering that SPE is more expensive than LLE, we used LLE for sample purification.…”
Section: Optimization Of the Sample Treatment Proceduresmentioning
confidence: 99%
“…Sample purification methods included LLE [30][31][32][33], and SPE [34][35][36][37]. Considering that SPE is more expensive than LLE, we used LLE for sample purification.…”
Section: Optimization Of the Sample Treatment Proceduresmentioning
confidence: 99%
“…DLLME was introduced by Rezaee et al. and has been applied to extract analytes from various matrixes . DLLME has appeared in different modes, such as vortex‐assisted dispersive liquid–liquid microextraction (VA‐DLLME) , ultrasound‐assisted dispersive liquid–liquid microextraction (USA‐DLLME) and SFODME .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, DLLME has proven one of the most versatile preconcentration methods to extract trace analytes from water samples. DLLME was introduced by Rezaee et al and has been applied to extract analytes from various matrixes [7][8][9][10][11][12][13][14][15]. DLLME has appeared in different modes, such as vortex-assisted dispersive liquid-liquid microextraction (VA-DLLME) [8], ultrasound-assisted dispersive liquidliquid microextraction (USA-DLLME) [9] and SFODME [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique properties, their use has attracted considerable interest, including an increasing number of publications on their use in preparing stationary phases of HPLC . An active research is found in many reports on the role of ILs to modify the retention of different types of solutes in LC . Based on their UV absorption, imidazolium ILs have been applied as background reagents for determination of IL cations in the HPLC and IC with UV indirect detection.…”
Section: Introductionmentioning
confidence: 99%